Women's Resilience in Building Family Resilience After Divorce in Silo Sub-District, Jember Regency - Sofiatul Jannah; Busriyanti; Muhammad Faisol (Syntax Corporation Indonesia, 2023)
Divorce is one of life's events that has significant impacts, not only on the divorcing couple but also on the families involved, especially the children. In this context, women often find themselves in a more vulnerable position as they frequently shoulder dual roles as mothers and workers. After a divorce, women often face substantial economic, social, and psychological pressures. The objective of this research is to describe and analyze the lives of women in Silo Subdistrict, Jember Regency, after divorce. The research approach chosen by the researcher is a legal research approach. This research was conducted in Silo Subdistrict, Jember Regency. The research subjects in this study included several single-parent women, widows, community figures (modin), and officials from Silo Subdistrict, Jember Regency. Data collection methods employed in this research included observation, interviews, and documentation. The researcher used a qualitative descriptive analysis technique in this study. The research findings indicate that the majority of single-parent women in Silo Subdistrict, Jember Regency, strive to meet their living needs by engaging in small-scale businesses such as selling cilok (Indonesian snack made from tapioca) and sausages, operating grocery stores and snack shops, and also selling vegetables. Additionally, some work as domestic assistants, overseas migrant workers (TKW), and engage in other activities, including labor work.